Is It Possible to Separate the Graft-Versus-Leukemia (GVL) Effect Against B Cell Acute Lymphoblastic Leukemia From Graft-Versus-Host Disease (GVHD) After Hematopoietic Cell Transplant? - Rozmus, Jacob; Bhatt, Sima T.; Buxbaum, Nataliya Prokopenko; Cuvelier, Geoffrey D. E.; Li, Amanda M.; Kitko, Carrie L.; Schultz, Kirk R. (Frontiers in Pediatrics, 2022)
Hematopoietic cell transplant is currently the only curative therapy for many pediatric patients with high risk acute lymphoblastic leukemia. Its therapeutic mechanism is primarily based on the generation of an alloreactive graft-versus-leukemia effect that can eliminate residual leukemia cells thus preventing relapse. However its efficacy is diminished by the concurrent emergence of harmful graft-versus-host disease disease which affects healthly tissue leading to significant morbidity and mortality. The purpose of this review is to describe the interventions that have been trialed in order to augment the beneficial graft-versus leukemia effect post-hematopoietic cell transplant while limiting the harmful consequences of graft-versus-host disease. This includes many emerging and promising strategies such as ex vivo and in vivo graft manipulation, targeted cell therapies, T cell engagers and multiple pharmacologic interventions that stimulate specific donor effector cells.